Pengaruh pengendalian internal terhadap pencegahan fraud dengan intervening good corporate governance - Agus Budi Hartono; Arief Himmawan Dwi Nugroho (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The more fraud committed by a company, whether owned by the government or private, encourages further research on the internal control system to prevent fraud. This study aims to determine and analyze the effect of internal control and good corporate governance on fraud prevention. This study uses data collection techniques by distributing questionnaires to BPR in the Semarang City with a total of 110 respondents. The this study uses data analysis techniques using multiple linear regression analysis techniques. The results of this study are internal control and good corporate governance have a significant effect on fraud prevention, and internal control has a significant effect on good corporate governance.